Hormoz: A Site Belonging to the Parthian to Islamic Periods in Khāsh County - Qaderi, Alireza; Nadooshan, Farhang Khademi; Kouhpar, Mehdi Mousavi; Neyestani, Javad; Haidari, Nozar (Anabasis. Studia Classica et Orientalia, 2012)
Essential factors in the formation, dynamics and broadness of settlement patterns are ecology and geomorphology. These elements have been taken into account in the archaeological surveys of Irandegan District of Khāsh County. A total of 63 sites were identified, most of which belong to Islamic and pre-Islamic historical ages. A few relics are datable to the pre-historical periods. Almost 70 percent of the registered sites are located along the Irandegan River. Regarding the obtained pottery data from the Hormoz site, we can suggest that the settlement history in this site could be traced back to the Parthian age and the settlement would continue its existence until the late centuries of the Islamic era.